THE USE OF CLOSE READING TECHNIQUE TO IMPROVE STUDENTS READING COMPREHENSION - Cecep Munawar Payumi; Yayu Fatimah Hartati (PROJECT (Professional Journal of English Education), 2018)
The main pupose of this study is to find out the effectiveness of close reading technique.  The research method used is quantitative research, or more specifically the one group pre-test post-test design. The sample of this study is eighth grade students of SMPS PGRI Warungkondang consist of 20 students. Data analysis indicates the mean scores between pre-test and post-test is 22, the tobs is 1.72  with the degrees of freedom (df) 19 and level of significance at 0.05 is 2.59. Based on data analysis the close reading technique has significant influence to improve students’ reading comprehension. Therefore, this technique is considered as a suitable technique for teacher as the strategy for teaching English.